Uncovering the Accounting Information System (AIS) Implementation in Pasar Mini Anugerah Yakin (PMAY) Grocery Store - Hassan, Haslinda; Amir Hussin, Muhammad Rosni; Mohamad Hsbollah, Hafizah; Abd Mutalib, Hafizah (2022)
This teaching case is a problem case related to Pasar Mini Anugerah Yakin (PMAY) grocery store. The grocery store was facing a dilemma whether its investment in the implementation of an accounting information system (AIS) in its grocery operation is worth the investment. The implementation of AIS in 2010 was aimed at expediting the business processes and maintaining proper records for tax and audit purposes. Hoping that the use of AIS would give them benefits, such as providing accurate and timely reports for making an informed decision, however, nothing much had been achieved after the ten years of its implementation. The business was still not able to use the AIS to the fullest where the use had been limited to the SmartPOS only. The other record-keeping was still done manually. Aware of the problems, the business believed that now was the ideal time for them to be on the right track, especially in making use of the AIS. Accordingly, this prompts researchers to investigate the matter and suggest possible solutions to fix the problems. The niche area of this case study is that it deals with the AIS implementation in microenterprises in the Malaysian retail industry.